2020
DOI: 10.1007/s10681-020-02585-y
|View full text |Cite
|
Sign up to set email alerts
|

A review on the genetic resources, domestication and breeding history of spinach (Spinacia oleracea L.)

Abstract: This paper addresses the genetic resources, domestication and breeding history of spinach as a comprehensive review of these crop aspects is currently unavailable. It is shown that the availability of genetic resources of wild relatives belonging to the primary gene pool is currently very limited, which hampers breeding and research activities. Therefore, new collecting expeditions are clearly warranted. The domestication of spinach is discussed on the basis of its presumed migration routes and the traits that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 102 publications
2
58
0
Order By: Relevance
“…Bold identifiers are used for the accessions from Iran, where spinach presumably has been domesticated the Western Asian landraces from the Caucasus. The genetic relationships between the reference cultivars are in line with their breeding history as Resistoflay has been developed from Viroflay by introgression of a downy mildew resistance, whereas Viking has resulted from a cross between Viroflay and the old European cultivar King of Denmark (Ribera et al 2020).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bold identifiers are used for the accessions from Iran, where spinach presumably has been domesticated the Western Asian landraces from the Caucasus. The genetic relationships between the reference cultivars are in line with their breeding history as Resistoflay has been developed from Viroflay by introgression of a downy mildew resistance, whereas Viking has resulted from a cross between Viroflay and the old European cultivar King of Denmark (Ribera et al 2020).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Despite their large similarity, the two wild species differ in inflorescence characteristics. Additionally, S. tetrandra male plants are considerably smaller than females, while this sexual dimorphism is not as pronounced in S. turkestanica (Ribera et al 2020). It has been suggested that one or both of these two species may have been ancestor of cultivated spinach (Andersen and Torp 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Individual effectors are usually not crucial for survival and there is redundancy in effector repertoires [200,309]. In Pfs, these dynamics lead to the continuous emergence of new races that break R-gene mediated resistance of newly bred spinach varieties [30,32]. The identification of Arabidopsis proteins that interact with Pfs effectors supports the idea of conserved plant targets across species (Chapter 3).…”
Section: The Search For Resistance Breaking Effectors In the Pfsmentioning
confidence: 99%
“…Peronospora effusa (Pfs) is an obligate biotrophic oomycete that causes downy mildew on spinach and is a major threat to spinach production worldwide [30,32]. Its hyphae can penetrate the leaf tissue and grow between plant cells, which they invaginate to form haustoria, the sites of interaction between the oomycete and plant cells [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation